A study to assess the role of contrast-enhanced multiphasic, multidetector computed tomography in the evaluation of renal lesions - Khantal, Dr. Nitin; P. Ahirwar, Laxman (International Journal of Medical Research and Review, 2020)
Aim: To assess the role of Contrast-Enhanced Multiphasic Multidetector Computed Tomography in the evaluation of renal lesions and its potential role in differentiating benign from malignant lesions. Material and Method: This prospective study was done in the Department of Radiodiagnosis Chirayu Medical College and Hospital Bhopal. A total of 100 patients to our department with strong clinical suspicion of renal lesions and those diagnosed by ultrasonography underwent Contrast-Enhanced Multiphasic Multidetector Computed Tomographic evaluation of abdomen using 64 Multislice Spiral CT scanner from August 2015 to July 2019. Results: The majority of patients presenting with renal lesions were each of the age groups <15 years and >40 years. Most of the patients were males 57%. The most common clinical complaint was renal colic 58(46%) and hematuria. The most common pathology was calculus 35(35%) second most common pathology was congenital anomalies 23(23%). The CT accuracy for detection of benign cystic lesion in this study was 94.7%, benign lesions were 92.6%and for malignant lesions was 86.6% in the present study. Conclusion: The accuracy of Contrast-Enhanced Multiphasic Multidetector Computed Tomography in detecting and characterizing renal lesions is high and it should be considered in the imaging workup of any patient with a renal complaint